Technological change, the productivity of formal and informal businesses, and the impact on labor market - Koffi Sodokin; Joseph Kokouvi Djafon; Mawuli Couchoro; Yao Mensah Kounetsron; Akoété Ega Agbodji (Cogent Economics & Finance, 2023)
Digital transformation, both omnipresent and influential, has deeply impacted various sectors with a particular focus on the economy. The introduction and adoption of tools that facilitate technological changes and online business practices have emerged as game changers. They have endowed corporations with enhanced internal agility and improved employee communications. Online business, with its vast potential, is becoming increasingly crucial in developing countries, where Internet accessibility is steadily growing. This study explores the impact of e-commerce on company productivity by considering both formal and informal sectors. It leverages data from the 2018 General Business Census of Togo. By applying endogenous switching regression and smoothed instrumental variable quantile regression tools, this study demonstrates that online businesses can significantly increase productivity, particularly in firms within the informal sector. However, this finding highlights the potential risk of job loss. This study concludes that support strategies are essential for promoting the integration of online companies, increasing productivity, and protecting jobs.
Keywords: L25; M15; O33; O55; 330; digital transformation; employment; online business; productivity